Characteristics and quantification of small microplastics (<100 μm) in seasonal svalbard snow on glaciers and lands - Rosso, Beatrice; Scoto, Federico; Hallanger, Ingeborg G.; Larose, Catherine; Gallet, Jean Charles; Spolaor, Andrea; Bravo, Barbara; Barbante, Carlo; Gambaro, Andrea; Corami, Fabiana (Journal of Hazardous Materials, 2024)
Small microplastics (SMPs < 100 mu m) can easily be transported over long distances far from their sources through the atmospheric pathways and reach even remote regions, including the Arctic. However, these sizes of MPs are mostly overlooked due to different analytical challenges; besides, their pathways through atmospheric depositions, such as snow depositions, are mostly unknown. The spatial variability in bulk snow samples was investigated for the first time in distinct sites (e.g., glaciers) near Ny angstrom lesund, the world-known northernmost permanent research settlement in the Svalbard Islands, to better comprehend the presence of SMP pollution in snow. Seasonal snow deposited over the tundra and the summits of different glaciers were also sampled. A sampling procedure was designed to obtain representative samples while minimizing plastic contamination, thanks to rigorous quality assurance and quality control protocol. SMPs' weight (mu g SMP L-1) and deposition load (mg SMPs m(-2)) result from being lower in the remote glaciers, where they may be subject to long-range transport. The SMPs' minimum length was 20 mu m, with the majority less than 100 mu m. Regarding their size distribution, there was an increase in the size length deriving from the local input of the human presence near the scientific settlement. The presence of some polymers might be site-specific in relation to the pathways that affect their distribution at the sites studied. Also, from the snow surface layer collected at the same sites to evaluate the variability of SMPs during specific atmospheric deposition events, the results confirmed their higher weight and load in surface snow near the scientific settlement compared to the glaciers. The results will enhance the limited knowledge of the SMPs in polar atmospheric compartments and deposition processes.